Pneumothorax - Amer, Khalid; Amer, Khalid (IntechOpen, 2019)
This book aims at reviewing contemporary publications on the subject of the pneumothorax. Specifically, the anatomy and physiology of the pneumothorax, the pathological classification into primary and secondary, the different methods of diagnosis, and the rationale behind the different approaches of management are discussed. Strategies for special circumstances are highlighted, such as the pneumothorax around menstrual cycles, during pregnancy, and before general anesthesia for other reasons, air travel, and scuba diving. Attention is drawn to the most contemporary trends of management and the evidence from recently published trials and reviews. A separate chapter is dedicated to controversies in the management of the pneumothorax. Trainees as well as established consultant thoracic surgeons, anesthetists, pulmonologists, pediatricians, obstetricians, and intensivists should find this book both interesting and provocative.
English
Keywords: Dermatology; Respiratory medicine